PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SD NEGERI 21 BALAI MAKAM DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Witmailen Witmailen; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observation that researchers do in the first semester of the school year 2015/2016, learning social studies test results found to identify the problem as follows: Low levels of student ability, the inability of students to complete the task, students are less able to appear in front of the class present the results of the group work and the lack of learning media as a supporter in the delivery of material. Subjects in this study is teacher and fifth grade students of SD Negeri 21 Balai Makam Saber Duri District of Bengkalis in the academic year 2016/2017, amounting to 32 students. In addition, the researchers used a type of classroom action research conducted in two cycles during 4 meetings. Each cycle is carried out through four stages, namely planning, action, observation, and reflection. The data collection technique is carried out through tests, observations, and documentation. The observation of the first meeting of the first cycle of teacher activity category of